The teaching evaluative practices and the formation of social imaginaries in teachers of basic secondary of the school our lady of bethlehem - Ramírez Rojas, Nelsy Gliced; Torres Claro, Jaider (Universidad Francisco de Paula Santander, 2017)
This article reports on research, the general objective of which was to establish whether or not there is arelation ship between teacher evaluation practices and the way in which they influence the creation of social imaginaries. For the development of the research, a qualitative methodology was taken into account, for which threeinstruments were used: a semi-structured interview applied to teachers, a classroom observation and a student survey.In order to analyze the information, a categorization and triangulation process was carried out, making use of the Atlas. ti software. It was concluded that the evaluation processes arestill traditional and that,although there is repeated talk of integral evaluation, it continues to focus on the cognitive. Similarly, in terms of the general objective, to knowif there is a relationship between the form of evaluation, teachers avoid the question and recognize that many of theirpracticesareinfluenced by the way they were evaluated,but at no time do they recognize that their form of evaluation can contribute to students changing their view of the world.